Aorto‐innominate artery bypass for migrated stent. Issue 1 (8th October 2020) - Chong, Jun Heng; Harky, Amer; Badran, Abdul; Panagiotopoulos, Nikolaos; Odurny, Allan; Philips, Michael; Livesey, Steven; Pousios, Dimitrios
Abstract: We report a case of a 64‐year‐old female who first presented with a transient ischemic attack in 2007 due to an innominate artery stenosis, which indicated an endovascular stent placement. In 2008, she presented with recurrence of symptoms and was diagnosed with in‐stent restenosis alongside an unusual occurrence of retrograde migration into the ascending aortic arch. We performed an aorto‐innominate bypass through a median sternotomy. The patient was discharged without any complications thereafter, and the graft has shown excellent patency. As of 2019, the patient remains well.